A Study of The Effect of Skeletal Class I and Class II of Malocclusion on Dental and Basal Arches Using Cone Beam Computed Tomography (CBCT) (Journal of Hama University, 2019)
The purpose of this study was to evaluate the effect of skeletal discrepancy on dental and basal arch dimensions in maxillary and mandibular jaws using CBCT.36 patients aged between (18-25) years, consisted of 12 patients of Class I malocclusion, 12 patients of Class II division 1 malocclusion and 12 patients of Class II division 2 malocclusion.Cephalometric imaging was taken, and ANB angle was measured to determine the antero-posteriar skeletal pattern, then CBCTs were taken and analyzed using EZ 3D plus software. Tips of cusps for dental measurements and basal bone center points for basal measurements were identified on upper and lower canines and first molarsDental and basal intercanine width, intermolar width and molar depth were measured.One-Way ANOVA analysis was used.This study shows statistically significant differences between the three groups of malocclusion in upper basal intercanine width and intermolar width, and upper and lower dental depth (P< 0.05).When studying the linear measurements differences in the maxilla, it showed that in skeletal class II division 1 cases, the measurements were statistically significant smaller in general than those in class I and class II division 2 cases in the basal intercanine and basal intermolar width but, the length of dental arches was statistically bigger in class II division 1.